Coupled electronic and magnetic relaxation in Fe1+yTe: direct evidence for the interaction between itinerant carriers and local moments. (28th October 2021) - Qian, B; Liu, J Y; Zhang, F M; Kong, F J; Zhou, W; Gu, Q C; Fang, Y; Han, Z D; Jiang, X F; Zhu, Y L; Wang, Y; Hu, J; et al.
Abstract: Iron chalcogenides are of particular interests among iron-based superconductors due to their distinct properties such as high- T c on FeSe monolayer and competing magnetic correlations in Fe1+ y Te. Here we report unusual transport properties observed near the critical composition of Fe1+ y Te ( y ∼ 0.09) where competing magnetic correlations exist. The resistivity exhibits surprising temperature-dependent relaxation behavior below T N, resulting in the increase of resistivity with time for 35 K < T < T N, but the decrease of resistivity with time for 10 K < T < 35 K. Such resistivity relaxation is intimately coupled to the magnetization relaxation and can be attributed to the glassy magnetic states induced by the competing magnetic orders. These findings demonstrate strong coupling between itinerant carriers and local ordered moments in Fe1+ y Te.